Mathematical model for analyzing the interrelation between monetary circulation and economic growth in developing countries - S. Yu. Malkov; O. I. Davydova (Russian Journal of Economics and Law, 2019)
Objective: to develop a basic mathematical model to assess the impact of foreign trade on the national economy and the impact of the national currency on economic growth in relation to developing countries.Methods: methods of mathematical dynamic modeling are used in the development of the model.Results: one of the most acute and unresolved problems for the Russian economy is the development of such currency-monetary policy that would provide opportunities for economic growth. One of the reasons for the ongoing disputes is the lack of a qualitative mathematical model that allows assessing its impact on economic processes. Mathematical models proposed by representatives of different economic scientific schools and describing the impact of monetization on the economy are considered. It is determined that the previously developed models are not applicable to the economies of developing countries. The characteristic is given of the dynamic mathematical model earlier developed by the authors describing cash flows in the Russian economy. The importance of models for developing economies is analyzed in terms of growth of the money supply and changes in the exchange rate of the national currency. As a result, it is determined that the constructed model, which is an aggregate version of the model of switching reproduction, takes into account the openness of the national economy and inflation processes. The model is tested on the example of currency-monetary policy of the USA and Russia. Scientific novelty: the model differs from analogues in that it is based on the modeling of cash flows in accordance with the methodology of modeling of switching reproduction, which allows analyzing the interaction of financial and real sectors of economy in developing countries.Practical significance: the model allows estimating the consequences of decisions in the field of currency-monetary policy in developing countries.